Measuring the Impact of the Investment Climate on Total Factor Productivity : The Cases of China and Brazil - Subramanian, Uma; Anderson, William P.; Lee, Kihoon (World Bank, Washington, DC, 2012)
This study measures the impact of investment climate factors on total factor productivity (TFP) of firms in Brazil and China. The analysis is conducted in two steps: first an econometric production function is estimated to produce a measure of TFP at the firm level. In the second step, variation in TFP across firms is statistically related to a indicators of the investment climate as well as firm characteristics. The results yield a number of insights about the factors underlying productivity. In both countries, and in a variety of industry groups, indicators of poor investment climate, especially delays in customs clearance and interruptions in utility services, have significant negative effects on TFP. Reducing customs clearance time by one day in China could increase TFP by 2-6 percent. Indicators such as email usage have positive effects on TFP. In the case of China, state-owned firms and firms located in the interior are shown to be much less productive than privately owned firms and firms located in the east. In Brazil, the results present an interesting contrast between the apparel industry and the electronics industry. In the apparel industry, older firms in competitive markets are more productive, while in the case of electronics, newer firms with higher market shares are more productive.